The Expectations of PJOK Teachers In Supporting The Acceleration of National Potential Young Athlete Training Centers (SLOMPN) - Kusmiyati Kusmiyati; Soegiyanto Soegiyanto; Hari Setijono; Soedjatmiko Soedjatmiko (Universitas Negeri Semarang, 2023)
The National Potential Young Athlete Training Center (SLOMPN) is a form of real implementation of the National Sports Grand Design (DBON). A special program which is the initial solution for a long-term national sports policy. Resources that have relevance and potential are the professional group of Physical Education, Sports and Health Teachers (PJOK). The PJOK teacher's personal, professional and social responsibility is a great potential to support the success of SLOMPN. The process of scouting initial talent and providing input for young sportsmen who are within the scope of the school, is an integral part of the SLOMPN system. The form of real roles that PJOK teachers can contribute is very much determined by the initial conditions of their expectations. This research aims to examine the direction and quality of PJOK Teacher expectations in the complete series of SLOMPN implementation. The research was carried out by conducting a random survey of the expectations of PJOK teachers in the Yogyakarta, Solo, Semarang (Joglosemar) areas through questionnaires (Google form). Several Focus Group Discussions (FGD) partially limited groups were conducted to obtain in-depth information and attitudes following up on questionnaire responses about expectations. The results of the research are that 81% of PJOK teachers in the 3 regions are willing to support the acceleration of SLOMPN, while 19% have not been involved in supporting the acceleration of SLOMPN.